Development of a single leg knee exoskeleton and sensing knee center of rotation change for intention detection - Moon, Dae Hoon; Kim, Donghan; Hong, Young Dae (Sensors (Switzerland), 2019)
In this study, we developed a single leg knee joint assistance robot. Commonly used exoskeletons have a left-right pair, but when only one leg of the wearer is uncomfortable, it is effective to wear the exoskeleton on only the uncomfortable leg. The designed exoskeleton uses a lightweight material and uses a wire-driven actuator, which reduces the weight of the driving section that is attached on the knee directly. Therefore, proposed exoskeleton reduces the force of inertia that the wearer experiences. In addition, the lower frame length of the exoskeleton can be changed to align with the complex movement of the knee. Furthermore, the length between the knee center of rotation and the ankle (LBKA) is measured by using this structure, and the LBKA values are used as the data for intention detection. These value helps to detect the intention because it changes faster than a motor encoder value. A neural network was trained using the motor encoder values, and LBKA values. Neural network detects the intention of three motions (stair ascending, stair descending, and walking), Training results showed that intention detection was good in various environments.
Keywords: Actuator system; Back-drivability; Compliant designs; Frame length; Intention detection; Lightweight materials; Motor encoders; Stair ascending; Algorithms; Ankle; Exoskeleton Device; Friction; Humans; Knee Joint; Leg; Neural Networks, Computer; ROC Curve; Rotation; Torque; Back-drivability; Compliant design; Intention detection; Knee exoskeleton; Modular exoskeleton; Neural network; Pattern recognition; Wire-driven actuator system